Use of a shared tuned mass damper (STMD) to reduce vibration and pounding in adjacent structures. - Abdullah, Makola M. (Earthquake engineering & structural dynamics.)
The dynamic response of tall civil structures due to earthquakes is very important to civil engineers. Structures exposed to earthquakes experience vibrations that are deterimental to their structural components. Structural pounding is an additional problem that occurs when buildings experience earthquake excitation. This phenomena occurs when adjacent structures collide from their out of phase vibrations. Many energy dissipation devices are presently being used to reduce the system response. Tuned mass dampers (TMD) are commonly used to improve the response of structures. The stiffness and damping properties of the TMD are designed to be a function of the natural frequency of the building to which it is connected. This research involves attaching adjacent structures with a shared tuned mass damper (STMD) to reduce both the structures vibration and probability of pounding. Because the STMD is connected to both buildings, the problem of tuning the STMD stiffness and damping parameters becomes an issue. A design procedure utilizing a performance function is used to obtain the STMD parameters to result in the best overall system response.